The (peculiar) economics of NCAA basketball - McFall, Todd A.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
The economics of the NCAA Division I men's basketball league are peculiar because it fails to hire the best college-aged players and does little to enhance competitive balance within the league. The league's policy decisions and its ability to remain economically viable, despite its short-sighted governance decisions, are discussed.
Keywords: Industries; Sports; Behavioral economics; Microeconomics; Industrial organization; Economic history